1986
DOI: 10.1073/pnas.83.6.1627
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus DNA contains a glucocorticoid-responsive element.

Abstract: It has recently been shown that hepatitis B virus (HBV) contains a transcriptional enhancer element. In order to determine whether this enhancer responds to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
2
7

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(209 citation statements)
references
References 44 publications
5
195
2
7
Order By: Relevance
“…This is of practical importance for these patients in view of the direct stimulatory effect of corticosteroids on HBV replication. 26,27 In the present study, we confirmed the previous observation that steroids can enhance the expression of HBsAg during a short-term culture of hepatocytes isolated from chronic HBV camers.12 Similar to cyclosporine, FK506 did not change significantly viral envelope expression in cultured hepatocytes. In the same in vitro system quantitation of intracellular HBV DNA showed no significant changes after 18 hours' culture, suggesting that the enhanced HBsAg expression in hepatocytes under these conditions may initially result from enhanced translation of viral protein, rather than immediate replication of the viral genome.…”
Section: Discussionsupporting
confidence: 89%
“…This is of practical importance for these patients in view of the direct stimulatory effect of corticosteroids on HBV replication. 26,27 In the present study, we confirmed the previous observation that steroids can enhance the expression of HBsAg during a short-term culture of hepatocytes isolated from chronic HBV camers.12 Similar to cyclosporine, FK506 did not change significantly viral envelope expression in cultured hepatocytes. In the same in vitro system quantitation of intracellular HBV DNA showed no significant changes after 18 hours' culture, suggesting that the enhanced HBsAg expression in hepatocytes under these conditions may initially result from enhanced translation of viral protein, rather than immediate replication of the viral genome.…”
Section: Discussionsupporting
confidence: 89%
“…[23][24][25] The high level of HBV viremia may be, at least in part, because of a glucocorticoid response element as part of its genome that appears to enhance the replicative efficacy of HBV. 26 However, we have not found a direct relationship between viremia level and severity of hepatitis in the liver graft; this finding seems to indicate a lack of a direct cytopathic effect of HBV in this situation and suggests that disease may be mediated by immune mechanisms. In fact, the immunosuppressive agents used to avoid allograft rejection also markedly disturb host defense mechanisms directed at the HBV.…”
Section: Discussioncontrasting
confidence: 68%
“…In the transplant setting, steroids, azathioprine, cyclosporine, and tacrolimus (FK 506) are commonly used to prevent graft rejection. In vitro, corticosteroid increases HBV DNA and RNA production by stimulating HBV transcription [70,71], by binding to the glucocorticoid responsive element (GRE), and augmenting the HBV enhancer I. In addition, the use of rituximab can effectively remove or suppress anti-HBs producing B cells and cause reactivation of HBV even in HBV immune patients.…”
Section: Chemotherapy or Immunosuppressive Therapy Related To Hbv Reamentioning
confidence: 99%
“…Among the chemotherapeutic agents used, corticosteroids and anthracyclines [1][2][3][4][5][6][7] are most frequently associated with HBV reactivation. The HBV DNA contains a glucocorticoid-responsive element that facilitates replication [70,71], while anthracyclines have been shown in vitro to stimulate HBV DNA secretion [99]. Hence, ''steroid free'' chemotherapy has been proposed to minimize the risk of HBV reactivation.…”
Section: Risk Factors Involved In Hbv Reactivationmentioning
confidence: 99%